On the 70th anniversary of the outstanding ukrainian histologist Alexander Lutsyk - Chelpanova , I.V.; Yashchenko , A.M. (Морфологія / Morphologia / Morfologìâ, 2024)
On May 2, 2024, Professor Alexander Lutsyk – histologist, long-term head of Histology and Embryology Department (1989-2020), Vice-Rector for International Relations (1997-2000), Vice-Rector for Research (2000-2014) of Danylo Halytsky Lviv National Medical University (LNMU) – celebrates his 70th anniversary. Research interests of Dr Lutsyk were directed predominantly towards the application of lectins as tools in experimental histology, embryology and pathomorphology. In 1974 he was among the first in Ukraine who used lectins as histochemical dyes to study organ and tissue carbohydrates under normal and various pathological conditions. In 1989 he established a unique lectin histochemistry laboratory at the Histology and Embryology Departmen, where a large count of interested morphologists underwent training through the next decades, resulting in more than 30 Phd and Dsci dissertations being completed and defended. Professor Lutsyk research activities and results were presented in two monographs – «Lectins» (1980) and «Lectins in Histochemistry» (1989), as well as the promotion of Dsci thesis. Almost simultaneously Alexander Lutsyk initiated preparation and publication of “Human histology”(1992) – the first modern histology and embryology textbook, written in Ukrainian language. This textbook got the State award of Ukraine (1994), and since then for more than 30 years has been used by students and lecturers of medicine and dentistry in the Ukrainian Universitiese, being five times re-edited (1993, 2003, 2010, 2013, 2015). In 1999 Dr Lutsyk with co-authors published «Atlas of Microanatomy of the Oral Cavity Organs», which in 2000 was awarded the Yaroslav Mudryy Prize of the Academy of Sciences of Higher Education of Ukraine. Also he was among the translators into Ukrainian language the International Histological Terminology (editions 1993, 2001, 2010), of Langman’s Medical Embryology (2001), Ganong’s Human Physiology (2002), Dorland’s Illustrated Medical Dictionary (editions 2003, 2007), Netter’s Human Anatomy (2004, 2009). The above didactic activities were crowned with publication by the leading Ukrainian histologists under the editorialshipment of Professor Lutsyk and Professor Chaikovskyi National textbooks «Histology. Cytology. Embryology» for medical and dental students and professionals. Since 2016, Alexander Lutsyk is the deputy editor of the journals «Proceedings of the Shevchenko Scientific Society. Medical sciences», member of the editorial board of the journals «Morphologia», «Lviv Medical Journal/ Acta Medica Leopoliensia», «Lviv Clinical Bulletin». Currently he is co-author of more than 400 publications of different levels, accounting for Hirsch index in Scopus database – 7, in Google Scholar – 13). Under Dr Lutsyk guidance were prepared and conferred 5 PhD and 2 Dsci dissertations. In September 2019, by the decision of the Presidium of the Scientific Society of Anatomists, Histologists, Embryologists, and Topographic Anatomists of Ukraine, Professor Alexander Lutsyk was awarded the highest distinction of this same Society – «The Golden Medal of V.O. Betz». In 2024, he received the first ever "For Merit in Morphological Science" order.